Key steps in unconventional secretion of fibroblast growth factor 2 reconstituted with purified components - Steringer, Julia P.; Müller, Hans-Michael; Unger, Sebastian; Nickel, Walter (eLife, 2017)
The first reconstitution of an unconventional secretory mechanism uncovered the molecular mechanism by which Fibroblast Growth Factor 2 is secreted from mammalian cells.
Gesehen am 26.08.2020